Knowledge and education in classical Islam: religious learning between continuity and change - Günther, Sebastian (Islamic history and civilization, 2020)
Volume. 1. Part I. Setting the Stage: 1. The Humanities through Islamic Eyes: The Beginnings / Wadad Kadi -- Part II. Prophetic Mission, Learning, and the Rise of Islam: 2. "Arcane Knowledge" Communicated in the Quran / Angelika Neuwirth -- 3. Muhammad as Educator, Islam as Enlightenment, and the Quran as Sacred Epic / Todd Lawson -- 4. Divine Inspiration, Storytelling, and Cultural Transfer: Muhammad's and Caedmon's Call / Gregor Schoeler -- 5. The Exercise of Theological Knowledge in the Church of the East, Provoked by Coexistence with the Muslims (Seventh Century CE) / MartinTamcke -- 6. Contributions of the Mawālī ("New Converts to Islam") to Education in Early Islam (in Arabic) / Jamal Juda -- Part III. Rational vs. Spiritual Approaches to Education: 7. How Do We Learn? Al-Fārābī's Epistemology of Teaching / Nadja Germann -- 8. Al-Fārābī and His Concept of Epistemological Hierarchy / Mariana Malinova -- 9. Educational Discourse in Classical Islam: A Case Study of Miskawayh's (d. 421/1030) Tahdhīb al-akhlāq / Yassir El Jamouhi -- 10. Teaching Ignorance: The Case of al-Ghazālī (d. 505/1111) / Paul L. Heck -- 11. Al-Rafīq qabl al-ṭarīq: Remarks on al-Ghazālī's View of Sufism as a Way of Learning Religion / Steffen Stelzer -- 12. "Only Learning That Distances You from Sins Today Saves You from Hellfire Tomorrow": Boundaries and Horizons of Education in al-Ghazālī and Ibn Rushd / Sebastian Günther -- 13. A Sufi as Pedagogue: Some Educational Implications of Rūmī's Poetry / Yoones Dehghani Farsani -- Part IV. Learning through History: 14. Ibn Isḥāq's and al-Ṭabarī's Historical Contexts for the Quran: Implications for Contemporary Research / Ulrika Mårtensson -- 15. Scholars, Figures, and Groups in al-Azdī's Futūḥ al-Shām / Jens Scheiner -- Part V. Literature as Method and Medium of Instruction:16. Education through Narrative in Rasāʼil Ikhwān al-Ṣafāʼ / Shatha Almutawa -- 17. Storytelling as Philosophical Pedagogy: The Case of Suhrawardī / Mohammed Rustom -- 18. The Masters' Repertoire (Mashyakha) and the Quest for Knowledge / Asma Hilali and Jacqueline Sublet -- 19. The Use of Verse as a Pedagogical Medium, Principally in the Teaching of Grammar / Michael G. Carter -- 20. Islamic Education Reflected in the Forms of Medieval Scholarly Literature: Jamʻ, Tāʼlīf, and Taṣnīf in Classical Islam / Alexey A. Khismatulin -- 21. Primary Schoolteachers between Jidd and Hazl: Literary Treatment of Educational Practices in Pre-modern Islamic Schools / Antonella Ghersetti -- 22. The Metaphor of the Divine Banquet and the Origin of the Notion of Adab / Luca Patrizi -- 23. Wisdom and the Pedagogy of Parables in Abraham Ibn Ḥasday's The Prince and the Ascetic / Jessica Andruss